Islam and Indonesian foreign policy under the Yudhoyono presidency / Akhmad Baihaqie - Akhmad , Baihaqie (2017)
The central question posed by this study is why Indonesian foreign policy during Yudhoyono administration, compared to the previous ones, came to embrace policy of active engagement with the issues of Muslim concerns? Using state level analysis that rests on the proposition that foreign policy begins at domestic situation and that external posture of state is determined mainly by the internal factor, this qualitative study attempted to search for the possible answer through dynamic relations between state and political Islam in Indonesia as the prime mover. Drawn mainly from library research and interview, it revealed that both Soekarno and Soeharto have sidelined political Islam from the central discourse of domestic politics. Parallel to that, Indonesian foreign policy has been neutralized from Islamic influence, blocking Islamist groups from advancing their political standing at the international forum. Yudhoyono administration, however, showed significant shift by adopting series of foreign policies that show significant interest in Muslim concerns. It was first time that Islamic glossaries entered foreign policy speeches, and diplomatic machinery often cited jargons such as moderate Muslim, rahmatan lil ālamīn, and ummatan wasaṭan. The fact that Indonesia is a country with Muslim majority has been transformed to be the source of Indonesia’s international identity, which consequently infused Indonesia to be involved in addressing various contemporary ummatic challenges, forging closer and strategic relations with the Middle East countries, mainly Saudi, as the cradle of Muslim civilization, and collaborating with Muslim organizations and intellectuals in formulating and implementing some of foreign policies. In doing so, Yudhoyono has made Islam, rather than being a liability, as foreign policy asset. Further, this study reveals that Yudhoyono’s resort to Islam due to two interrelated matters: the increasing importance of Islam in domestic politics in Indonesia, and the increasing level of state’s confidence towards Islam, both of which consequently permit the Islamic nuance to be present in Indonesian foreign policy. The gradual proximity between state and Islam created harmonious and constructive relations, enabling Islam to make inroads in informing foreign policy, either dialectically through the Muslim pressure to the government, or peacefully by voluntary state’s reception to incorporate Muslim aspirations.